Mental Health Determinants Among a Psychiatric Outpatient Sample of Vietnamese Migrants in Germany - Wolf, Simon; Hahn, Eric; Wingenfeld, Katja; Nguyen, Main Huong; von Poser, Anita; Nguyen, Thi Hoa; Hanewald, Bernd; Böge, Kerem; Bajbouj, Malek; Dettling, Michael; Nguyen, Van Tuan; Ta, Thi Minh Tam (Frontiers in Psychiatry, 2020)
Background: Mental health risk-factors for Asian migrants have been studied almost exclusively in the US, Canada and Australia but not in European countries. Therefore, we aimed to identify sociodemographic, clinical and migration-surrounding factors associated with experienced mental distress among Vietnamese migrants in Germany. Method: 305 Vietnamese migrants utilizing Germany's first Vietnamese psychiatric outpatient clinic filled out at admission the Brief-Symptom-Inventory 18 (BSI-18) as well as a questionnaire on 22 potential mental health determinants. Using a multiple linear regression model, we identified those sociodemographic, clinical and migration-surrounding factors that were significantly related to the Global Severity Index (GSI) of the BSI-18. Results: The factors unemployment (B = -6.32, p = 0.014), financial problems (B = -10.71, p < 0.001), no or only little religious involvement (B = -3.23, p = 0.002), no psychiatric precontact (B = -7.35, p = 0.004), previous migration experiences (B = 8.76, p = 0.002), and perceived discrimination (B = 6.58, p = 0.011) were found to significantly increase the level of mental distress according to the BSI-GSI. Conclusion: Based on these results, we were able to construct a mental health risk-profile for Vietnamese migrants in Germany, which aims to detect candidates for psychiatric problems earlier and supply them with customized prevention and therapy options.